Are FXR Family Proteins Integrators of Dopamine Signaling and Glutamatergic Neurotransmission in Mental Illnesses? - Khlghatyan, Jivan; Beaulieu, Jean-Martin (Frontiers in Synaptic Neuroscience, 2018)
Dopamine receptors and related signaling pathways have long been implicated in pathophysiology and treatment of mental disorders. Dopamine signaling may impact neuronal activity by modulation of glutamate neurotransmission. Recent evidence indicates a direct and/or indirect involvement of fragile X related family proteins (FXR) in the regulation and mediation of dopamine receptor functions. FXRs consists of fragile X mental retardation protein 1 (Fmr1/FMRP) and its autosomal homologs Fxr1 and Fxr2. These RNA-binding proteins are enriched in the brain. Loss of function mutation in human FMR1 is the major genetic contributor to Fragile X mental retardation syndrome. Therefore, the role of FXR proteins has mostly been studied in the context of autism spectrum disorders. However, recent genome-wide association studies have linked this family to schizophrenia, bipolar disorders and mood regulation pointing toward a broader involvement in mental illnesses. FXR family proteins play an important role in the regulation of glutamate-mediated neuronal activity and plasticity. Here, we discuss the brain-specific functions of FXR family proteins by focusing on regulation of dopamine receptor functions, ionotropic glutamate receptors mediated synaptic plasticity and contribution to mental illnesses. Based on the recent evidence we propose that FXR proteins are potential integrators of dopamine signaling and ionotropic glutamate transmission.